Tourism as a Driver of Soft Power: The Case of South Korea - Quijano Herrera, Jessica L.; Pérez-Tapia, Gema (Springer Nature, 2024)
In recent years, Korea has become more well known due to the expansion of its culture and entertainment industries. According to the four regions proposed by Ooi (Encyclopedia of Tourism. Springer, Cham, Switzerland, pp. 1–2, 2016), (i) Tourism has increased knowledge about Korea, fostering empathetic understanding and familiarity with the destination. (ii) The principal goal of the tourism authority is to enhance Korea's reputation as a tourist destination. (iii) Korea has organized and invested in several events, exhibitions, and games that serve as a major tourist draw, thereby enhancing its geopolitical position. (iv) Through their behavior in the destination country, foreign tourists reflect the image of their home country, so altering preconceived notions of the other countries. This paper examines how tourism has become a driver of the country's soft power, taking into account the shift in the rebranding of the country toward the cultural and entertainment industry “Hallyu” and the country's ability to design public policies that promote attractive and accessible tourism for international visitors. In addition to their ability to organize large-scale events, the peninsula has demonstrated its political, social, and economic development to the world. Additionally, the manner in which tourism has been approached during and after COVID has made it possible to maintain the confidence of tourists and capitalize on the popularity of Hallyu stars as a clear strategy to attract tourists and position the country as a tourist destination, thereby boosting tourism and, consequently, enhancing soft power.
Keywords: Corea del Sur; Turismo; Poder; Relaciones internacionales; Soft Power; Korea; Tourism; Hallyu